The impact of an ethics training programme on the success of clinical ethics services. (March 2014) - Dörries, Andrea; Simon, Alfred; Vollmann, Jochen; Neitzke, Gerald
The interdisciplinary Hannover Qualification Programme on ethics consultation has trained hospital staff to operate clinical ethics services in their respective hospitals since 2003. To evaluate Hannover Qualification Programme, all former participants were contacted using an online questionnaire including four domains: status quo before attending Hannover Qualification Programme, present status, impact of Hannover Qualification Programme, future challenges. Research objectives were the long-term satisfaction with Hannover Qualification Programme and its impact on clinical ethics services. The response rate was 45% (167/369). Hannover Qualification Programme was evaluated as helpful and the responders were capable of applying their acquired skills. Most participants could contribute to the implementation of clinical ethics services. They were satisfied with Hannover Qualification Programme and with the degree of changes in their hospitals. In conclusion, clinical ethics education had long-term effects on trainees and on their respective hospitals. Problems were mentioned rather in the field of utilisation than with implementation or quality of clinical ethics services.